Tekno Ekonomi Pemanfaatan Biogas Berbasis POME untuk Pembangkit Listrik, Bahan Bakar Boiler, dan BioCNG - Dwi Lukman Hakim; Novio Valentino (Jurnal Sains dan Teknologi, 2019)
Utilization of biogas for electricity generation, boiler fuel, and for vehicle fuel must consider the technicaland economic feasibility. This paper discusses the economic feasibility of using biogas for these 3 scenarios bytaking a special case to be applied in a palm oil mill in Riau Province. The calculation results show that the useof POME (palm oil mill effluent) biogas for these three scenarios is feasible. Indicators of financial feasibilityshow a positive NPV value and an IRR value higher than the discount rate. Between the three scenarios, thescenario of utilizing biogas into electricity is the most feasible scenario to be implemented based on the value ofits feasibility indicators, namely with an IRR value of 14.22%, NPV of Rp. 11,474,070,468and a project paybackperiod of 9 years 2 months. However, based on the investment costs and operational costs, the scenario of usingbiogas for boilers is easier to implement because it requires lower costs, with an investment cost of Rp.20,267,641,460and an annual operational cost of Rp. 898,517,546. The selection of biogas utilization scenariosalso needs to consider obstacles from the technical aspects as well as the marketing aspects of the product. Theuse of biogas for electricity has obstacles to the sale of electricity to PLN. Meanwhile, the use of biogas forbioCNG requires investment in converter kits for vehicles and the estimated price of bioCNG cannot competewith the CNG prices on the market.